THRIFT SHOPPING SEBAGAI GAYA HIDUP MAHASISWA TANJUNGPINANG - Eka Putri Lestari; Siti Arieta; Sri Wahyuni (LPPM STISIP Persada Bunda, 2024)
The phenomenon that is happening now is that female students are competing to show an attractive appearance through thrift shopping. The purpose of this study was to find out Thrift Shopping as a Lifestyle for Tanjungpinang Students and in this study used Chaney's theory (2009:41). The method in this study the authors used a qualitative descriptive research type where in this study used 10 informants with interview and observation data collection techniques. Based on the results of the research, it is known that it is found that the attitude of students buys goods because the prices are much cheaper and the benefits they get are the same as buying new clothes. Students feel lucky because they get goods with well-known brands, students believe that what they wear will be a concern and identity for themselves, therefore some prefer branded items, rather than buying new clothes that are not branded. The conclusion in this study is thrift shopping as a lifestyle for Tanjungpinang students. In this case, students carry out thrifting with the aim of getting clothes with well-known brands besides that clothes with well-known brands are considered to have good quality. Therefore, in doing thrifting, it is clear to get branded and quality clothing, regardless of the main function of clothing is to cover and protect the body.